Multispectral camera design and algorithms for python snake detection in the Florida Everglades - Vaca-Castano, Gonzalo; Driggers, Ronald; Furxhi, Orges; Arvidson, Carl; Mazzotti, Frank (SPIE, 2019)
The Burmese Python has invaded the Florida Everglades where the estimate of pythons is around 150,000 and rapidly growing. Pythons were released as unwanted pets in South Florida and now they are an apex invasive species. As a result, the local fauna population has been largely decimated, and there is an increasing concern about python migration to northern latitudes. Working with a team interested in developing a python detection camera, we have taken hyperspectral and multispectral reflectivity measurements of Brumese Pythons in the visible and near infrared bands (VisNIR). The results show that some VisNIR reflectivity bands can be used to automatically discriminate pythons in the wild. This paper discusses the results of our data collections and provides a camera design process that includes a band selection algorithm and pixel-level classification using machine learning. Additionally, we show a visual enhancement alternative that helps to identify pythons in realistic conditions.